Systematik der mitteleuropäischen Myzinae, mit besonderer Berücksichtigung der im Deutschen Entomologischen Institut befindlichen Sammlung Carl Börner (Homoptera: Aphidoidea - Aphididae). III. Teil. Myzini, Cryptomyzini und Nasonoviini (Textfig. 87-131). - Heinze, Kurt (Contributions to Entomology = Beiträge zur Entomologie, 1961)
Systematic details are given of the subfamily Myzinae, which contains many vectors of phytopathogenic viruses and which is for this reason of special interest in phyto-pathology. The numerous figures - in most cases drawings from type specimens of the "Börner-collection" or from aphids determined by Börner, may facilitate in future the recognition of aphids of this group. Essentially the systematic interpretation of Börner, as published in "Europae centralis Aphides" (1952), was accepted and this especially with regard to Myzodes for M. persicae (Sulz.) and the species which belong to this genus (s. str.). In some cases the interpretation of Börner concerning scientific names of aphids was out of date or was not sufficient established. Here may be mentioned Myzotoxoptera Theob. and related genera and species. 7 genera (or subgenera respectively) and 3 species are new to science; these are Pseudobrevicoryne n. g., Cavaraiellopsis n. g., Cavaraiellia n. subg., Lipamyzodes n. g., Spinas pidaphis n. g., Pseudo-rhopalosiphoninus n. g., Arthromyzella n. g., Myzus alectorolophi n. sp., Spinaspidaphis droserae n. sp. and Hyperomyzus crepidis n. sp. Diphorodon C. B., Sciamyzus Stroyan, Prunomyzus H.R.L. & Rogers, Galiobium C. B. and Submegoura H.R.L. are considered to be genera and not to be subgenera (in their original sense). Myzella G. B. does not fall into Cryptomyzus C. B., as Hille Ris Lambers thinks, it is a particular genus (sensu G. B.). On the other hand I can not follow the opinion of Börner, that Acanthulipes C. B. belongs to Trichosiphonaphis Tak. The Tribe Nasonoviini is divided into Nasonoviina and Rhopalosiphonina n. Subtrib. In many cases new host plants could be added to the description of aphid species; this is remarkable for some aphid species of mosses. Nomenclatural Acts Pseudorhopalosiphoninus Heinze, 1961 (Aphididae), gen. n. Spinaspidaphis Heinze, 1961 (Aphididae), gen. n. crepidis Heinze, 1961 (Hyperomyzus), spec. n. alectorolophi Heinze, 1961 (Myzus), spec. n. droserae Heinze, 1961 (Spinaspidaphis), spec. n.